Performance based seismic engineering the need for a reliable conceptual comprehensive approach. - Bertero, Raul D. (Earthquake engineering & structural dynamics.)
The main objectives of this paper are : (i) to review briefly as to what is understood by performance based engineering, performance based seismic engineering and performance based seismic design (PBSD); (ii) to discuss the main requirements that a reliable PBSD should satisfy and why some approaches that have been proposed fail in satisfying those requirements; (iii) to focus on what is considered a promising probabilistic PBSD approach; and (iv) to present a conceptual comprehensive numerical procedure for the PBSD of buildings. It is shown that to satisfy the objectives of a reliable PBSD philosophy and procedure it is necessary to start with a multi level seismic design criteria, to consider a probabilistic design approach, to consider local structural and non structural damage and therefore design spectra for buildings (n degrees of freedom), to take into account the cumulative damage, and to control not only displacements but also ductility (minimum strength) to limit damage. Finally, it is concluded that a transparent and conceptual comprehensive preliminary design approach is necessary.